A Pilot Study of a Creative Bonding Intervention to Promote Nursing Students' Attitudes towards Taking Care of Older People - Ann R. Lamet; Rosanne Sonshine; Sandra M. Walsh; David Molnar; Sharon Rafalko (Nursing Research and Practice)
Although numbers of older people are increasing, nursing students have negative attitudes towards older people and do not plan to care for them following graduation. Multiple strategies have been implemented to reverse students' attitudes with mixed results. The purpose of this pilot quasi-experimental study was to test a Creative-Bonding Intervention (CBI) with students implementing art activities with older people to promote students' willingness to take care of them. Using a self-transcendence conceptual framework, control (𝑛=56) and experimental (𝑛=14) student groups were pre- and post-tested on attitudes toward older people, self-transcendence, and willingness to serve. The CBI improved attitudes towards older people with negative attitudes significantly changed (𝑃=.008) but with no significant differences on self-transcendence and willingness to serve. However, willingness to serve results approached significance (𝑃=.08). The willingness measure (one question) should be expanded. Curricula changes that incorporate creative activities such as the CBI with larger and equal numbers in student groups and longitudinal follow up to determine long-term results after graduation are suggested.